2019
DOI: 10.1016/j.oooo.2018.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Panoramic radiography is of limited value in the evaluation of maxillary sinus disease

Abstract: Objectives. The aim of this study was to determine (1) the diagnostic efficacy of orthopantomography (OPG) in the diagnosis of sinus diseases by using cone beam computed tomography (CBCT) as the imaging gold standard, (2) which diseases can be diagnosed by using panoramic radiography or CBCT, and (3) the interobserver agreement of 2 experienced dental radiologists. Study Design. The images of 714 individuals who underwent OPG and CBCT on the same day were assessed separately by 2 dental radiologists. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 17 publications
1
25
1
5
Order By: Relevance
“…Constantine et al suggested that panoramic imaging has poor e ciency in nding the problems of maxillary sinuses, presenting a result of 36.7% sensitivity and 51.9% NPV. 27 However, higher sensitivity and NPV of panoramic radiographs were measured in the present study resulting in higher accuracy. Conversely, the accuracy of lateral and postero-anterior cephalograms was signi cantly lower than that of the reference, implying a low diagnostic value of cephalograms for detecting maxillary sinus ndings.…”
Section: Discussioncontrasting
confidence: 51%
“…Constantine et al suggested that panoramic imaging has poor e ciency in nding the problems of maxillary sinuses, presenting a result of 36.7% sensitivity and 51.9% NPV. 27 However, higher sensitivity and NPV of panoramic radiographs were measured in the present study resulting in higher accuracy. Conversely, the accuracy of lateral and postero-anterior cephalograms was signi cantly lower than that of the reference, implying a low diagnostic value of cephalograms for detecting maxillary sinus ndings.…”
Section: Discussioncontrasting
confidence: 51%
“…Constantine et al suggested that panoramic imaging has poor efficiency in finding the problems of maxillary sinuses, presenting a result of 36.7% sensitivity and 51.9% NPV 37 . However, higher sensitivity and NPV of the panoramic radiographs were measured in the present study resulting in higher accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the histopathological study is mandatory. A radiological study must be performed using a CT/CBCT and not a panoramic x-ray since it offers less diagnostic sensitivity [3]. Drumond and Cols [5] performed a study exclusively using a CT in order to evaluate the prevalence of different illnesses in 762 maxillary sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the histopathological study is mandatory. A radiological study must be performed using a CT/CBCT and not a panoramic x-ray since it offers less diagnostic sensitivity [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation